Vernetzte Bankenwelt. Computerisierung in der Kreditwirtschaft der Bundesrepublik und der DDR - Schmitt, Martin (Wege in die digitale Gesellschaft. Computernutzung in der Bundesrepublik 1955-1990)

Über Mehrsprachigkeit und Migration nachdenken und sprechen. Migrationspädagogische Perspektiven auf den Einsatz sog. Migrationsliteratur im Deutschunterricht - Büttner, Denise

Dokumentation der Auftaktveranstaltung zur 2. Förderphase von ProDaZ - Büttner, Denise

Numerical analysis of partial differential equations on and of evolving surfaces - Kovács, Balázs

Zwischen studentischer Diversität und fachlicher Homogenisierung. Die wertbezogene Hochschuldidaktik als Vermittlerin im Habituskonflikt - Reis, Oliver (Hochschuldidaktik forscht zu Vielfalt und Offenheit Profilbildung und Wertefragen in der Hochschulentwicklung I)

Понять, как они тикают [Verstehen, wie sie ticken]. Interview on CLIL conducted by Ирина Долженко [Irina Dolzhenko] on behalf of sib.fm - Dolzhenko, Irina; Rumlich, Dominik

Radar backscattering from a large-grain cometary coma: numerical simulation - Dogra, Shraddha; Grynko, Yevgen; Zubko, Evgenij; Förstner, Jens (Astronomy & Astrophysics)
We numerically simulate the circular polarization ratio of the radar signal backscattered from a large-grain cometary coma and compare the simulation results with the radar measurements for seven comets. We apply the discrete dipole approximation method and a model of random irregular particles. Our results confirm water ice composition of the cm-sized chunks detected by the NASA Deep Impact space probe in the vicinity of the nucleus of Comet 103P/Hartley 2. The index of the power-law size distribution in this case can be constrained to the range n ≈ 3.3–4.3. For the other considered comets the circular polarization ratio can be reproduced with variations of the power index between 2 and 5.
Keywords: tet_topic_scattering

Hybrid coupled-mode modeling in 3D: perturbed and coupled channels, and waveguide crossings - Hammer, Manfred; Alhaddad, Samer; Förstner, Jens (Journal of the Optical Society of America B)
The 3D implementation of a hybrid analytical/numerical variant of the coupled-mode theory is discussed. Eigenmodes of the constituting dielectric channels are computed numerically. The frequency-domain coupled-mode models then combine these into fully vectorial approximations for the optical electromagnetic fields of the composite structure. Following a discretization of amplitude functions by 1D finite elements, pro- cedures from the realm of finite-element numerics are applied to establish systems of linear equations for the then- discrete modal amplitudes. Examples substantiate the functioning of the technique and allow for some numerical assessment. The full 3D simulations are highly efficient in memory consumption, moderately demanding in com- putational time, and, in regimes of low radiative losses, sufficiently accurate for practical design. Our results include the perturbation of guided modes by changes of the refractive indices, the interaction of waves in parallel, horizontally or vertically coupled straight waveguides, and a series of crossings of potentially overlapping channels with fairly arbitrary relative positions and orientations.
Keywords: tet_topic_waveguide; tet_topic_numerics

Direction-tunable enhanced emission from a subwavelength metallic double-nanoslit structure - Song, Xiaohong; Wang, Nini; Yan, Ming; Lin, Cheng; Förstner, Jens; Yang, Weifeng (Optics Express)
Controlling light emission out of subwavelength nanoslit/aperture structures is of great important for highly integrated photonic circuits. Here we propose a new method to achieve direction-tunable emission based on a compact metallic microcavity with double nanoslit. Our method combines the principles of Young’s interference and surface plasmon polaritons interference. We show that the direction of the far-field beam can be controlled over a wide range of angles by manipulating the frequency and relative phase of light arriving at the two slits, which holds promise for applications in the ultracompact optoelectronic devices.
Keywords: tet_topic_plasmonics

Subtleties in Security Definitions for Predicate Encryption with Public Index - Blömer, Johannes; Liske, Gennadij (Proceedings of the International Conference of Mathematical Aspects of Computer and Information Sciences (MACIS))